Análisis y plan de mejora energético del centro de diagnóstico automotor Ivesur Colombia Tolima - Cortes Rodríguez, Cristian David (Universidad Antonio Nariño, 2021)
vesur Colombia Tolima, is an Automotive Diagnostic Center (CDA) that provides the mechanical technical review service and pollutant emissions, has an accreditation certificate issued by the National Accreditation Body (ONAC). The CDA committed to the environmental well-being of the region has set as one of its objectives to implement an Energy Management System (EMS) and to take a first step towards sustainable development policies in relation to the efficient use of energy. The document presents the energy audit within the theoretical framework, the purpose of which is to quantify consumption to plan and propose an efficient improvement plan based on national and international standards such as NTC.ISO 50001